Cultural dimension as an influencer factor on work statisfaction / Nurul Hazirah Keria - Nurul Hidayah, Keria (2018)
Among the factors that lead to an increasing number of resignations are often due to management problem, unhappy workplace, and lack of career advancement opportunities where workers do not feel fulfilled or satisfied with their working environment. Happy and satisfied employees are also important towards improving productivity. Thus, many organizations have increased their efforts to improve employee work satisfaction, which is especially true for organizations in developing countries. An important step in improving work satisfaction is to understand if a worker is satisfied with his/her working environment which differs from one organization to another. However, understanding work satisfaction of the employees is challenging due to the influence of cultural values or dimension. Hence, the objective of this study is to identify the correlation between the cultural dimensions and work satisfaction of the employee of University of Malaya. Fifty subjects were surveyed based on six cultural dimensions; Power Distance Index (PDI), Individualism versus Collectivism (IDV), Masculinity versus Femininity (MAS), Uncertainty Avoidance Index (UAI), Long Term Orientation versus Short Term Normative Orientation (LTO), and Indulgence versus Restraint (IND). The results showed that (1) Uncertainty Avoidance Index (UAI); r = 0.535, (2) Power Distance Index (PDI); r = 0.456 and (3) Indulgence vs Restrain (IND); r = 0.427 are correlated with work satisfaction. These findings contribute to an understanding that cultural dimension have influences on work satisfaction and can assists in improving employee’s performance evaluation to increase their work efficiency and productivity.